Epistemological Foundation of ESG-Based Investment in Indonesia's Economic Policy - Putri Dwi Wahyuni; Mohammad Mukhtasar Syamsuddin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research focuses on the application of ESG (Environmental, Social, and Governance) based investments in Indonesia, which emerged in response to the increasing global awareness of environmental and sustainability issues. While ESG in Indonesia is growing, many companies have yet to fully adopt these principles effectively, and there are epistemological challenges in understanding and translating ESG standards into the local policy context. The purpose of this research is to deeply analyze the concept and implementation of ESG-based investment from an epistemological perspective in Indonesian public policy. This research wants to identify the extent to which the Indonesian government understands and utilizes ESG-related information in investment policy and evaluate the effectiveness of the policy. The type of research is descriptive quantitative using a philosophical approach with literature study as a secondary data source, including policy documents, government reports, and academic publications related to ESG. The data is explored using concept analysis and existing theories to assess the application of ESG in economic policy. The findings show that although Indonesia has ESG-related policies, their implementation is often influenced by international pressure and legitimacy needs rather than real impact on sustainability. ESG policies in Indonesia also risk becoming a tool of “greenwashing,” where companies use it for image without concrete actions. This research recommends increased transparency and accountability in ESG reporting for such policies to deliver substantial change.